Gerbang logika X-OR pada pandu gelombang optik single mode y-branching dengan menaruh sebagian bahan tak-linier di dalam cladding - mutmainnah, mutmainnah (Universitas Negeri Semarang, 2020)
An Optical Logic X-OR gate in Y-Branching single mode waveguide which nonlinear material superimposed partially in the cladding region was analyzed by means of FD-BPM (Finite Difference Beam Propagation Method). The whole proposed waveguide dimension is 50 x 3900 µm and for each fixed parameters such as film width w = 2.0 µm, angle θ = 0.2290, film refractive index nf =1.552, cladding refractive index nc=1.550, λ=0.5145 µm, nonlinear coefficient (partially superimposed in the cladding region) a = 6.377x10-12 m2/V2 and propagation constant β/k0 =1.55087373. Scheme of laser intensities propagation from input channel to the output channel showed that the yield of the optical logic X-OR gate exhibited the following output powers.